Diagnóstico ambiental no distrito de Cachoeira, no município de Candói (PR), realizado com estudantes do ensino médio - Grittem, Silvana (2016)
The present dissertation aimed to carry out an environmental diagnosis based on environmental perceptions of secondary students of the rural college state of Cachoeira, located in the municipality of Candói, in Paraná State, Brazil. In this study we aimed to the rapprochement between the environmental perception and Environmental Education, to consider the needs of participatory diagnosis and in tune with the reality experienced by study participants. The survey allowed incorporate the potential environmental impact of the province of waterfall and a glimpse of other dimensions related to the perceptions of students, such as the aesthetics, the appreciation of nature, respect and also the involvement in the face of environmental issues, in particular the water in the local context. To understand the logic of relations that the research participants establish with your living space was conducted a survey of the history of the municipality of Candói. Were also investigated data on the population and the geography of the city. This information was important to support the diagnosis made. The data collection was done in two steps. First, we used the implementation of structured questionnaire, which dealt with issues related to perception of the environment and on the quality, use and management of water. n the second stage of data collection was used the technique of focus groups, which allows the understanding of the processes of construction of the reality experienced by a social group, their daily practices, attitudes and behaviors that are relevant to the study. Thus, the data analysis allowed to know the relations that those involved in this study establish with your life, revealed by means of perceptions, meanings and experiences. The results showed that the research participants have a link with affective local nature, however, demonstrate significant concerns with the state of the environment, particularly in the waters of the place where they live, to understand the relationships between social phenomena and the problems linked to water. In this way, proved to have an understanding of the importance and conservation of water, adopting social practices are responsible and in line with environmental education. Among the environmental problems raised, what stands out is the pollution of soil and water bodies by the intense use of agrochemicals, the fate of sewage effluents, the lack of riparian vegetation in rivers and the lack of protection of springs. The results also point to the possibility of further studies that may be directed to educational issues, environmental, management of water resources, planning and regional development. It is inferred that the Environmental Education, supported by the environmental perception and environmental diagnostics, you can set up an important support for coping of socioenvironmental crisis today.